Bacterial ACC deaminase: Insights into enzymology, biochemistry, genetics, and potential role in amelioration of environmental stress in crop plants - Shahid, Mohammad; Singh, Udai B.; Khan, Mohammad Saghir; Singh, Prakash; Kumar, Ratan; Singh, Raj Narian; Kumar, Arun; Singh, Harsh V. (Frontiers in Microbiology, 2023)
Growth and productivity of crop plants worldwide are often adversely affected by anthropogenic and natural stresses. Both biotic and abiotic stresses may impactfuture food security and sustainability; global climate changewill only exacerbate the threat. Nearly all stresses induceethylene production in plants, which is detrimental to their growth and survival when present at higher concentrations. Consequently, management of ethylene production in plants is becoming an attractive option for countering the stress hormone and its effect on cropyield and productivity.In plants, ACC (1-aminocyclopropane-1-carboxylate) serves as a precursor for ethylene production. Soil microorganisms and root-associated plant growth promoting rhizobacteria (PGPR) that possess ACC deaminase activity regulate growth and development of plants under harsh environmental conditions by limiting ethylene levels in plants; this enzyme is, therefore, often designated as a ‘stress modulator.’ TheACC deaminase enzyme, encodedby the AcdS gene, is tightly controlled and regulated depending upon environmental conditions. Gene regulatory components of AcdS are made up of the LRP protein-coding regulatory gene and other regulatory components that are activated via distinct mechanisms under aerobic and anaerobic conditions. ACC deaminase-positive PGPR strains can intensively promote growth and development of crops being cultivated under abiotic stressesincluding salt stress, water deficit, waterlogging, temperature extremes, and presence of heavy metals, pesticides and other organic contaminants. Strategies for combating environmental stresses in plants, and improving growth by introducing the acdS gene into crop plants via bacteria, have been investigated. In the recent past, some rapid methods and cutting-edge technologies based on molecular biotechnology and omics approaches involving proteomics, transcriptomics, metagenomics, and next generation sequencing (NGS) have been proposed to reveal the variety and potential of ACC deaminase-producing PGPR that thriveunder external stresses. Multiple stress-tolerant ACC deaminase-producing PGPR strains have demonstrated great promise in providing plant resistance/tolerance to various stressors and,therefore, it could be advantageous over other soil/plant microbiome that can flourish under stressed environments.